The Representation Ahok’s Leadership Style in The Jakarta Post News: Critical Discourse Analysis (Representasi Gaya Kepemimpinan Ahok di Koran The Jakarta Post: Analisis Wacana Kritis) - Novia Resti Junaidi; Endry Boeriswati; Liliana Muliastuti (Indonesian Language Education and Literature, 2018)
This study aims to determine Ahok’s leadership style in The Jakarta Post news of 2014-2015 editions. This is a qualitative research using a critical discourse analysis based on the Norman Fairclough’s model. In this research the ideology is analyzed in terms of discoursive and socio-cultural practices in the news. The research was analysed by finding out ideologies in discourse practices including texts production, ideologies, socio-cultural practices and attention to social cultural aspects. Leadership theories used in this research range from autocratic, democratic, liberal, bureaucratic to situational leadership styles. The research results show Ahok’s dominant autocratic leadership style in The Jakarta Post news of 2014-2015 editions. As The Jakarta Post was not neutral in fostering the ideology, many authors supported Ahok’s leadership ideology in the news. The socio-cultural practices delineate that Ahok’s autocratic leadership style and policies as a governor are unsuitable with socio-cultural spheres in Indonesia. Therefore, his leadership style got more contras than pros from the public. This research is expectedly useful for learners and readers in understanding and analyzing hidden intentions in a discourse, especially to open up the ideology of a leader. Penelitian ini bertujuan untuk menentukan gaya kepemimpinan Ahok melalui berita di The Jakarta Post edisi 2014-2015. Penelitian ini menggunakan analisis kritis model Norman Fairclough. Ideologi dianalisis dalam bentuk praktik diskursif dan sosial budaya yang terdapat dalam berita. Data penelitian diperoleh dengan mencari ideologi yang terdapat dalam praktik diskursus, termasuk produksi teks, ideologi, praktik sosial budaya, dan perhatian terhadap aspek sosial budaya. Teori kepemimpinan yang digunakan, meliputi: gaya kepemimpinan otokratis, demokratis, liberal, birokratis, dan situasional. Hasil penelitian menunjukkan bahwa gaya kepemimpinan Ahok yang dominan dalam berita The Jakarta Post edisi 2014-2015 adalah otokratik. Hal ini karena The Jakarta Post tidak netral dalam mengembangkan ide-ide ideologis. Banyak penulis yang mendukung ideologi kepemimpinan Ahok yang tertuang dalam berita. Praktik-praktik sosial budaya menunjukkan bahwa gaya kepemimpinan dan kebijakan Ahok yang otokratis tidak sesuai dengan lingkup sosial budaya di Indonesia. Oleh karena itu, gaya kepemimpinan Ahok mendapat lebih banyak kontradiksi daripada penerimaan di kalangan masyarakat.